Pembatalan Perkawinan Dalam Kasus Poligami Tidak Tercatat Yang Perkawinannya Telah Putus Akibat Kematian - Salsabiela, Riskhi; Prananda, Rahandy Rizki (Fakultas Syariah INSURI Ponorogo, 2023)
Marriages can be annulled when they do not comply with the provisions of the Marriage Law. Parties involved in a marriage can request an annulment of the marriage because there was a misunderstanding in the form of identity falsification or unrecorded polygamy, for example in Decision Number 2479/Pdt.G/2020/PA.JU. This lawsuit was filed by the first wife to annul the marriage between the second wife and her deceased husband whose marriage had been broken up due to death. The issue lies in the legitimacy of filing for an annulment of a marriage that has ended due to death and the legal consequences of the decision in this case. This study utilized the Normative Juridical method by examining literature studies. The results of the study indicate that the basis for the annulment proposed by the plaintiff is valid based on three articles: Article 27 paragraph (2) and Article 24 of the Marriage Law, as well as Article 71 letter a Compilation of Islamic Law. There are two legal consequences resulting from this decision, the husband and wife relationship, and joint assets.